PEER-REVIEWING ARGUMENTATIVE ESSAYS IN AN EFL CONTEXT: INSIGHTS FROM A MOODLE-BASED WORKSHOP. - MANDICI, Mădălina Elena (Studii de Ştiintă şi Cultură)
This article presents a case study examining the design, implementation, and outcomes of a large-scale peer-review workshop conducted via Moodle in the context of a second-year BA English language course at "Alexandru Ioan Cuza" University of Iași (UAIC), Romania. The activity engaged 248 English majors and minors in writing and peer-assessing argumentative essays, accounting for 20% of their final grade. Drawing on a rubric-based assessment comprising eight criteria (thesis, exigence, supporting arguments, language range and accuracy, audience awareness, source quality, source use, and citation), the study explores the effectiveness of peer assessment as both a pedagogical strategy and an assessment instrument. Quantitative results show consistency in peer-assigned grades, albeit with evidence of leniency, while qualitative findings indicate limited critical depth in the feedback provided. The discussion situates these findings within the wider literature on peer review, feedback literacy, and EFL argumentative writing, reflecting on the tension between the formative potential of peer review and its use in graded assessment. The article concludes with practical implications for implementing peer review in large EFL cohorts and outlines possible directions for refining rubric design and student training.